Era Baru Pendidikan: Pemanfaatan Teknologi Dalam Mencapai Tujuan Pendidikan Indonesia - Supriatna, Chandra (Indo-MathEdu Intellectuals Journal, 2024)
This article discusses the important role of technology in expanding access to education, improving the quality of learning, and strengthening teacher performance in the digital era. This study uses a qualitative approach with a literature study method. The sources of research data are scientific journals, research reports, articles, and official government websites. Data were obtained and selected based on their suitability with the focus of the research, the credibility of the data source, and the accuracy of the research method. Data analysis was carried out qualitatively consisting of data reduction, data presentation and conclusion drawing. The results of the data analysis show that technology facilitates distance learning and digital platforms, providing access to education for students in remote areas and those with limitations. Adaptive learning platforms and technology-based learning media provide personalized and effective learning experiences, while online training platforms and digital resources help teachers improve their abilities and knowledge. With the wise and optimal use of technology, we can build an inclusive, high-quality, and adaptive learning ecosystem, producing the next generation of the nation that is superior and ready to advance the Indonesian state